Product Marketing to Increase Knowledge and Skills of ME Smoothies MSMEs in Bandar Lampung - Intan Lidiya Widuri; Mahrinasari MS; Yuniarti Fihartini; Khairunnisaa Khairunnisaa; Sri Hartati; Afrida Jayanti; Ranti Dwi Octaviani (MINOVa Ditria Jaya, 2025)
The purpose of this paper is to explore the impact of community service activities in the form of product marketing digitalization on increasing the knowledge and skills of ME Smoothies MSME players in Bandar Lampung. This study aims to assist MSME players in utilizing digital media to increase competitiveness and expand market reach. The approach used is a participatory approach through a series of activities in the form of needs analysis, intensive training, and mentoring in the use of digital technologies such as social media, e-commerce, and marketing software. This activity involves MSME participants who are actively running their businesses and is evaluated through observation, interviews. The findings show that this program succeeded in improving the ability of participants in managing social media accounts and digital platforms, creating promotional content, and registering their products on food delivery services. Within one month, partners experienced a 30% increase in sales turnover as well as a significant increase in digital interactions. This study is still limited to one MSME partner and does not include a long-term evaluation of the sustainability of the use of digital technology. Nevertheless, this activity provides a real picture of the importance of digital education to improve the competitiveness of MSMEs. This program directly contributes to the empowerment of MSMEs through applicable digitalization strategies. The results of the activity can be used as a training model for other MSMEs that have limited access to technology and marketing. This activity encourages the economic independence of MSME actors and strengthens the community's adaptation to technological changes in the digital era. This approach also strengthens the position of MSMEs as drivers of the local economy. Keywords Digitalization, Product Marketing, MSMEs